EFFECT OF WATERING FREQUENCY AND ORGANIC FERTILIZER ON THE GROWTH AND YIELD OF GROUND NUT - Supriyono, Supriyono; Rizkyah, Berliana Nur; Budiastuti, Maria Theresia Sri; Setyaningrum, Desy (Journal of Biodiversity and Biotechnology, 2024)
Groundnut (Arachis hypogaea) is one of the commodities with high economic value; however, weather anomalies can affect plant water availability, which in turn impacts groundnut production and productivity. If water availability is not balanced with proper fertilizer application, plant growth may be inhibited. This study aims to determine the role of watering frequency and organic fertilizer on the growth and yield of ground nut. The research was conducted at the Laboratory of the Faculty of Agriculture, Sebelas Maret University, located in Sukosari Village, Jumantono District, Karanganyar Regency for a duration of four months, from December 2024 to March 2025. The method used was a factorial Randomized Complete Block Design (RCBD), consisting of two factors and three replications. The first factor was watering frequency (once a day, once every two days, once every three days, and once every four days). The second factor is the organic fertilizer dosage (0; 10; 20; and 30 tons.ha -1). Data were analyzed using Analysis of Variance (ANOVA) at a 95% significance level, followed by Duncan’s Multiple Range Test (DMRT) at a 95% significance level. Regression analysis was performed to determine the recommended dosage, and correlation analysis was used to identify relationships between observed variables. The result showed that watering once every three days resulted in the best 100-seed weight. Watering once a day resulted in the best dry biomass weight. Organic fertilizer dose of 20 t.ha-1 produced the best plant height, leaf area, leaf area index, number of pods, fresh pod weight, dry pod weight, number of seeds, and seed weight. Organic fertilizer dose of 30 t.ha -1 produced the best number of leaves at 5 Weeks After Planting (WAP), number of nodes at 5 WAP, and flowering age. Interaction between watering once a day and organic fertilizer dose of 20 t.ha-1 produced the best dry biomass weight.